Urban development problems in the Algerian city - Ouahiba SAHBI (Social Sciences Journal, 1970)
This article deals with urban development issues in general and the one tha tconcerns the Algeriancity in particular takingintoac countit's social, economic and cultural specialities tha tdifferentiateitfrom the other societies ,and thisrequires development programs that respect the fundamentals andthe social and the cultural environment of the urban reality and all the structural problems of theAlgerian urban society.